(untitled) (Jurnal Pustaka, 2026)
This study aims to determine the history of the establishment of the Mu’allimin Muhammadiyah Sawah Dangka Tahfizhul Qur’an Islamic Boarding School, analyze the role of leadership in its development process in 2007–2022, and identify factors that influence this development. This study uses the theoretical basis of the history of Islamic education, the concept of Islamic boarding schools, and the theory of the role and development of educational institutions. The method used is the historical research method with the stages of heuristics, verification, interpretation, and historiography. Data collection was carried out through interviews, observation, and documentation, with relevant primary and secondary sources. The results of the study show that the Islamic boarding school was established in 2007 and developed gradually through each leadership period, marked by an increase in the number of students, the construction of facilities, and the strengthening of the Tahfizhul Qur’an education system. The role of leadership has a significant influence on the direction of policy and management of the institution. The development of the Islamic boarding school is influenced by internal and external factors, including support from Muhammadiyah and the community.